SCN5A mutation is associated with severity of abnormalities detected by ECG imaging in Brugada syndrome. (19th May 2022) - Pannone, L; Monaco, C; Sorgente, A; Gauthey, A; Calburean, P-A; Overeinder, I; Bala, G; Almorad, A; Stroker, E; Pappaert, G; Sieira, J; Brugada, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Brugada syndrome (BrS) is caused by mutations in SCN5A gene in 15%-20% of cases. Previous studies showed a worse prognosis in SCN5A mutation carriers (SCN5A+). Purpose: To evaluate genotype-phenotype correlation with ECG imaging (ECGI). Methods: All consecutive patients who underwent ECGI with CardioInsight for BrS were retrospectively analyzed. ECGI parameters analyzed before and after ajmaline administration were: 1) Right ventricular outflow tract (RVOT) activation time (RVOT-AT) and 2) RVOT recovery time (RVOT-RT). Genetic analysis was performed in all patients with SeqCap EZ Human Exome Probes v3.0 for BrS. Patients were defined as SCN5A+ if they had a pathogenic/likely pathogenic mutation in SCN5A following ACMG guidelines. Results: Thirty-six BrS patients were included and 8 patients (22%) were SCN5A+. At baseline ECGI map, mean RVOT-RT was higher in SCN5A+ [384.8 ms vs 362 ms, p=0.037], with no difference in RVOT-AT (p=0.65). After ajmaline administration SCN5A+ patients showed higher RVOT-AT [125.6 ms vs 102.4 ms, p=0.045] (Figure) and higher RVOT-RT [426.4 ms vs 400 ms, p=0.038]. At univariate logistic regression, baseline RVOT-RT was a predictor of SCN5A mutation (specificity: 0.64, sensitivity 0.88, AUC 0.75). Conclusion: In BrS syndrome SCN5A+ patients exhibit marked depolarization and repolarization abnormalities as assessed by ECGI.